Initialization scheme of the trusted execution environment based on the user card - Lei WANG; Meng LU (Dianxin kexue)
Smartphones with a trusted execution environment (TEE) has an authority issue of the certificate with the loading stage.Based on the analysis of the initialization architecture and initializing scheme of the trusted execution environment,by using trust chain technology,a scheme was proposed to initialize the trusted terminal of the operator's card as the trusted root,and ideas were provided for the telecom operators to use the user card resources to participate in the construction of the industrial chain of the trusted execution environment.